Pengaruh Metode Brainstorming Terhadap Keaktifan Belajar Siswa pada Mata Pelajaran Pendidikan Agama Kristen di SMP Negeri 1 Saipar Dolok Hole Tahun Pembelajaran 2023/2024 - Dian Lorensa Ritonga; Raikhapoor Raikhapoor; Julita Herawati; Sandy Ariawan; Goklas J. Manalu (Simpati, 2024)
The research aims to determine the positive influence of the brainstorming method on students' active learning in Christian Religious Education subjects at SMP Negeri 1 Saipar Dolok Hole for the 2023/2024 academic year. The research hypothesis is that there is a positive influence between the brainstorming method on students' active learning in Christian Religious Education subjects at SMP Negeri 1 Saipar Dolok Hole for the 2023/2024 academic year. The population of all students at SMP Negeri 1 Saipar Dolok Hole for the 2023/2024 academic year who are Protestant Christians is 46 people. This research is population research. The research instrument is a closed questionnaire. The results of data analysis obtained: The value rcount=0.535>rtable=0.291 shows that there is a positive relationship between the brainstorming method and students' active learning in Christian Religious Education subjects. Regression equation. Hypothesis test Fcount=17.68>Ftable=3.23 then H0 (null hypothesis) is rejected and Ha (alternative hypothesis) is accepted. The research concluded that there was a positive and significant influence between the brainstorming method on students' active learning in Christian Religious Education subjects at SMP Negeri 1 Saipar Dolok Hole for the 2023/2024 academic year.